PH‐Switchable Water‐Soluble Boron Nitride Nanotubes. Issue 32 (27th August 2018) - Guan, Jingwen; Kim, Keun Su; Jakubinek, Michael B.; Simard, Benoit
Abstract: The first example of aqueous solutions of boron nitride nanotubes (BNNTs) with switchable stability and without use of surfactants is demonstrated. The as‐produced boron nitride nanotubes are both purified and solubilized through an environmentally friendly and scalable approach using water extraction and liquid bromine treatment. This treatment effectively removes elemental boron particles and excess bromine reacts with BNNTs, inducing B−N bond cleavage on the BNNT surface to yield hydroxyl (OH) and amino (NH2 ) functionalized BNNTs. The resulting functionalized BNNTs form stable aqueous solutions around neutral pH (4 < pH < 8), but readily precipitate in other pH ranges. This switchable solubility is explained in terms of the capability of the functional groups (OH and NH2 ) to form hydrogen‐bonding networks in water. Further, the solubility differences in selected polar organic solvents have been utilized to prepare functionalized BNNTs with higher purity. Abstract : The first example of pH‐switchable water‐soluble boron nitride nanotubes (BNNTs) is obtained from an environmentally friendly 3‐stage purification process for as‐produced BNNTs. The resulting OH/NH2 ‐functionalized BNNTs are soluble around neutral pH and also extractable with some polar organic solvents to further the purification of BNNTs over 95 wt%.